2015
DOI: 10.1007/s00393-015-1598-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of anti-MCV and anti-CCP antibodies in rheumatoid arthritis

Abstract: Our meta-analysis demonstrates that anti-MCV is more sensitive but less specific, and has lower diagnostic accuracy than anti-CCP in RA, although anti-MCV and anti-CCP showed comparable high PLRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…In a previous meta-review, which summarized 12 studies on the diagnostic accuracy of anti-CCP assays, the area under the curve for the discrimination of 1988 patients with RA from 1740 disease controls without RA was 0.817 based on pooled sensitivities and specificities of 0.634 and 0.955, respectively. 17 Our study has a limitation in that we could not estimate diagnostic performance of the evaluated assays according to RA stages because we were unable to obtain sufficient clinical information on patients with RA, including the degree of arthralgia and the number of affected joints because of the retrospective study design. We could not investigate the correlation between results of the anti-CCP assays and clinical manifestations either.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous meta-review, which summarized 12 studies on the diagnostic accuracy of anti-CCP assays, the area under the curve for the discrimination of 1988 patients with RA from 1740 disease controls without RA was 0.817 based on pooled sensitivities and specificities of 0.634 and 0.955, respectively. 17 Our study has a limitation in that we could not estimate diagnostic performance of the evaluated assays according to RA stages because we were unable to obtain sufficient clinical information on patients with RA, including the degree of arthralgia and the number of affected joints because of the retrospective study design. We could not investigate the correlation between results of the anti-CCP assays and clinical manifestations either.…”
Section: Discussionmentioning
confidence: 97%
“…In early RA, anti-MCV sensitivity and specificity (64% and 97%) are higher than those of RF [99]. A recent meta-analysis, which included a total of 12 studies and 2003 RA patients, demonstrated a higher sensitivity of anti-MCV (68.6%) than anti-CCP (61.7%) in the diagnosis of RA, although anti-MCV specificity (94.2%) remained lower than that of anti-CCP (97.1%) [100]. High levels of anti-MCV antibodies seem to predict a rapid erosive disease in early RA and have been associated with active disease and worst outcomes [101,102].…”
Section: Additional Autoantibodiesmentioning
confidence: 97%
“…In our patient's case, she had a history of RA for many years and her serologic testing showed a markedly elevated RF and anti-CCP to support RA as an accurate pre-existent diagnosis [9]. In the current case, no biopsy was performed to confirm diagnosis because of the high clinical suspicion of RA pachymeningitis and risks outweighed the benefits in a clinically improving patient.…”
Section: Discussionmentioning
confidence: 61%